Congenital hypothyroidism, cardiac defects, and pancreatic agenesis in an infant with GATA6 mutation. Issue 6 (24th March 2020) - Raghuram, Nikhil; Marwaha, Ashish; Greer, Mary‐Louise C.; Gauda, Estelle; Chitayat, David
Abstract: GATA6 pathogenic variants primarily manifest a phenotype with pancreatic agenesis and cardiac malformations. However, additional congenital malformations affecting the biliary system, congenital diaphragmatic hernia and developmental delay have been reported. We report a newborn, prenatally diagnosed with truncus arteriosus and intrauterine growth restriction, who was postnatally found to have pancreatic agenesis associated with neonatal diabetes and hepatobiliary abnormalities. Whole exome sequencing identified a de novo, heterozygous mutation in the GATA6 gene (c.1366C>T; p.Arg456Cys). Further investigations revealed abnormalities not previously associated with GATA6 mutation, including unilateral thyroid lobe agenesis associated with congenital hypothyroidism, absent gall bladder, possible adrenal insufficiency, thrombocytopenia, and neonatal stroke.